Effects of Bacillus subtilis KG109 on Growth Performance, Carcass Quality, Serum Indicators, Intestinal Morphology, and Digestive Enzymes in Broilers - Hong Chen; Weixin Liu; Hao Zhang; Yibo Yan; Meiqi Chen; Xiaoling Ding; Cheng Zhang; Runsheng Jiang; Zaigui Wang (Animals)
The purpose of this experiment is to investigate how different doses of Bacillus subtilis KG109 powder affect the growth performance, carcass quality, serum biochemical indexes, serum antioxidant and immunological index, intestinal morphology, and digestive enzyme activity of broilers. Four hundred chicks of a similar weight (1 day old) are randomly assigned to four groups of five replicates of 20 chicks each (half males and half females). The control group is fed a basal ration, and the experimental groups T1, T2, and T3 are supplemented with 6.0 × 108 CFU/kg, 1.2 × 109 CFU/kg, and 1.8 × 109 CFU/kg of Bacillus subtilis KG109 bacterial powder, respectively, in the basal ration. The feeding cycle is 52 d. Compared with the control group, Bacillus subtilis KG109 powder (1) increases the broiler feed conversion ratio (FCR) (p < 0.05), (2) improves the carcass quality (slaughter rate, cooking loss, L* and b* values) (p < 0.05), (3) enhances the serum biochemical indexes (alanine transaminase (ALT), alkaline phosphatase (ALP), aspartate transaminase (AST), albumin (ALB), and triglycerides (TG)) (p < 0.05), (4) improves the serum antioxidant capacity (total an-tioxidant capacity (T-AOC), total superoxide dismutase (T-SOD), and glutathione peroxidase (GSH-PX)) and immunoglobulins (lg A, lg G, lg M) (p < 0.05), (5) improves the intestinal morphology (villus height and villus height to crypt depth (VCR)) (p < 0.05), and (6) increases the intestinal digestive enzyme activities (amylase, protease, and lipase) (p < 0.05). In summary, adding Bacillus subtilis KG109 to broiler diets can result in a significant decrease in broilers’ FCR, an increase in their slaughtering rate, a decrease in their serum ALT, ALP, and AST activities, an increase in their serum TG content, an improvement of their immune and antioxidant capacity, an improvement of their intestinal morphology, and an improvement of their intestinal digestive enzyme activity. It is recommended to add 1.8 × 109 CFU/kg of bacteria.